An evaluation of the equilibrium value of the euro, its predecessors and their constituent currencies based on economic fundamentals. Issue 33 (15th July 2017) - Grossmann, Axel; Paul, Chris; Simpson, Marc W.
ABSTRACT: This study presents constructed equilibrium exchange rates (EERs) of the euro and its predecessors the European Unit of Account and the European Currency Unit, as well as the euro's member states using a relative version of purchasing power parity (PPP) equilibrium. The revealed patterns of over- and undervaluation demonstrate how well suited the northern member states, in contrast to the southern states, were for the monetary union. Moreover, a relative persistent overvaluation for Greece and Portugal suggests that their ambition to join the euro reduced their competitiveness. The constructed EERs of the euro suggest the European Commission was able to set the initial value of the euro with a high degree of accuracy. Furthermore, the EERs indicate a successive strengthening of the fundamental value of the euro versus the U.S. dollar from 1999 to 2015. The analysis shows a close correlation between the deviations from equilibrium and the events of Greece's sovereign debt crisis. In addition, the presented graphs show strong support for the PPP hypothesis. The results are robust to different constructed EERs and offer a guide to international market participants interested in the general equilibrium path of the euro and its predecessors.